The Correlation between Pre-operative Leukocyte Levels and Length of Stay in Appendicitis Patients after an Appendectomy at Dr. Zainoel Abidin Hospital 2019–2020 - Yusuf, Muhammad; Kulsum, Kulsum; Gianty, Jauza Aqilla (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Appendicitis is an inflammation of the vermiform appendix. The infectious process and the inflammatory response are associated with increased leukocyte levels. Leukocyte levels can be used as the predictor of severity, treatment selection, and outcome of appendicitis patients that affect the length of hospitalization. AIM: The aims of the study are to determine the correlation between pre-operative leukocyte levels and the length of stay in appendicitis patients after an appendectomy at Dr. Zainoel Abidin Hospital 2019–2020. METHODS: The study was an observational analytic study with a cross-sectional design. The sampling technique used is total sampling. The data collected were sourced from medical records and obtained from 47 research subjects. RESULTS: The results showed that both appendicitis patients with leukopenia (<5000 cells/mm3) and normal (5000–10,000 cells/mm3) consist of two subjects which required a short length of hospitalization (<5 days). In the patient with leukocytosis Grade I (≤18,000 cells/mm3), 23 subjects (92%) required a short length of hospitalization and 2 subjects (8%) required a long hospitalization (≥5 days). Meanwhile, patients with leukocytosis Grade II (>18,000 cells/mm3), 8 subjects (40%) required a short length of hospitalization, and 12 subjects (60%) required a long hospitalization . Based on the bivariate analysis using the Chi-square method, obtained p = 0.002 (p < 0.05). CONCLUSION: There was a correlation between preoperative leukocyte levels and the length of stay in appendicitis patients after an appendectomy at dr. Zainoel Abidin Hospital.